Implementing information strategy planning in an enterprise - Md Dahalin, Zulkhairi (Penerbit Universiti Utara Malaysia, 2007)
Information Strategy Planning is about formulating an Information System strategy for the enterprise by developing a high-level overview model of the enterprise’s information requirements. This overview model is the enterprise’s information architecture or blueprint which aims at aligning the enterprise’s business strategy with its Information Technology (IT) strategy. This book provides a practical guide to implementing Internet Service Provider (ISP) in an enterprise. It gives a complete understanding of the approach, tools and techniques used to carry out an ISP study. A real-life case study company is used to provide actual learning experience and it should be a useful lesson for those contemplating on conducting an ISP study. Real life scenarios with limitations and pitfalls are combined with ideal situations so that lessons can be learnt to avoid common mistakes and alert potential failures as well as to highlight best practices. This book also provides reference to the Malaysian Government Manpower and Modernization Planning Unit (MAMPU) Information and Communication Technology (ICT) Strategic Plan Guideline and the MAMPU ISP Template Version 1.0 which are the main reference documents for government ministries and agencies embarking on an ISP study. Though the format of this book is not based on the guideline and the template, much of the main sections in the guideline and the template are covered in detail in this book.